1992
DOI: 10.1111/j.1751-1097.1992.tb04208.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivation of Hypericin Generates Singlet Oxygen in Mitochondria and Inhibits Succinoxidase

Abstract: Photosensitized inhibition of mitochondrial succinoxidase by hypericin was measured in vitro and found to be drug-dose, light-dose, and wavelength dependent. Singlet oxygen generation, monitored using the singlet oxygen trap tetramethylethylene, and oxygen consumption in isolated mitochondria sensitized by hypericin were also light-dose and wavelength dependent. Unequivocal evidence for the generation of singlet oxygen was obtained using kinetic isotope ratios of products from the reaction between singlet oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(86 citation statements)
references
References 44 publications
2
84
0
Order By: Relevance
“…This indicates instability of the cytoplasmic membranes when associated with hypericin. Thomas et al (1992) have shown that through a process of singlet oxygen generation, photoactivation of hypericin inhibits succinoxidase activity of mitochondria isolated from bovine heart. The high affinity of hypericin for membranous cellular organelles suggests that hypericin may act also at the mitochondrial level in whole cells.…”
Section: Antiviral Activity Of Hypericin Against Hsv-1 87mentioning
confidence: 99%
“…This indicates instability of the cytoplasmic membranes when associated with hypericin. Thomas et al (1992) have shown that through a process of singlet oxygen generation, photoactivation of hypericin inhibits succinoxidase activity of mitochondria isolated from bovine heart. The high affinity of hypericin for membranous cellular organelles suggests that hypericin may act also at the mitochondrial level in whole cells.…”
Section: Antiviral Activity Of Hypericin Against Hsv-1 87mentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11] In addition, hypericin has attracted attention for its antidepressant activity. [12][13][14][15] The interaction of light with hypericin and hypericin-like chromophores is clearly of fundamental biological importance.…”
Section: Introductionmentioning
confidence: 99%
“…For the majority of the photosensitizer drugs the mechanism of action is connected with Type I (production of radicals) and Type II (production of singlet oxygen) photodynamic processes. It has been shown that antiviral and antitumoral photo-activities of Hyp are oxygen dependent [5][6]. However, others and we have suggested "an alternative" origin for the photo-induced activity of Hyp.…”
Section: Introductionmentioning
confidence: 93%